Highlights of the 12th International Bordetella Symposium - Locht, Camille (2020)
To commemorate the 100th anniversary of the Nobel prize being awarded to Jules Bordet, the discoverer of Bordetella pertussis, the 12th International Bordetella Symposium was held from 9 to 12 April 2019 at the Universite Libre de Bruxelles, where Jules Bordet studied and was Professor of Microbiology. The symposium attracted more than 300 Bordetella experts from 34 countries. They discussed the latest epidemiologic data and clinical aspects of pertussis, Bordetella biology and pathogenesis, immunology and vaccine development, and genomics and evolution. Advanced technological and methodological tools provided novel insights into the genomic diversity of Bordetella and a better understanding of pertussis disease and vaccine performance. New molecular approaches revealed previously unrecognized complexity of virulence gene regulation. Innovative insights into the immune responses to infection by Bordetella resulted in the development of new vaccine candidates. Such discoveries will aid in the design of more effective approaches to control pertussis and other Bordetella-related diseases.